South‐South Irregular Migration: The Impacts of China's Informal Gold Rush in Ghana. (11th October 2018) - Botchwey, Gabriel; Crawford, Gordon; Loubere, Nicholas; Lu, Jixia
Abstract: This article examines irregular South‐South migration from China to Ghana, and the role it played in transforming livelihoods and broader developmental landscapes. It looks at the entry of approximately 50, 000 Chinese migrants into the informal small‐scale gold mining sector from 2008‐2013. These migrants mainly hailed from Shanglin County in Guangxi Province. In Ghana, they formed mutually beneficial relationships with local miners, both legal and illegal, introducing machinery that substantially increased gold production. However, the legal status of Chinese miners was particularly problematic as, by law, small‐scale mining is restricted to Ghanaian citizens. In mid‐2013, President Mahama established a military task force against illegal mining, resulting in the deportation of many Chinese miners. The article examines the experiences of both Chinese migrants and Ghanaian miners. Findings are that irregular migration into an informal sector had long‐lasting impacts and played a significant role in the transformation of economic, political, and physical landscapes in Ghana.